Pengaruh Pengalaman, Komitmen Dan Orientasi Etika Pada Sensitivitas Etika Auditor - Asana, Gde Herry Sugiarto; Suartana, I Wayan; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.03.NO.04.TAHUN 2014, 2014)
Ethical sensitivity is very important and capabilities needed by the auditors in performing their duties. The purpose of this study was to determine the effect of experience, professional commitment, organizational commitment, idealism, and relativism on ethical sensitivity auditor Public Accountant Office in Bali. Experience is measured by position, long work, improving skills and training ( Gusnardi, 2003). Commitment can be divided into professional and organizational commitment (Bline et al, 1991). Ethical orientation shaped by idealism and relativism (Forsyth, 1980). The study was conducted in 2013. The data was collected using a questionnaire. The number of samples in this study were 60 auditors and selected by purposive sampling method, which has a minimum of 1 year of audit experience. The analysis technique used is multiple linear regression. The research instrument has passed the test of validity and reliability. Regression models also have passed the test of classical assumptions. Statistical analysis showed that the variables of experience, professional commitment, organizational commitment, idealism, and relativism effect on ethical sensitivity. Adjusted R Square value of 0.820 indicates that the variation in changes in ethical sensitivity auditor Public Accountant Office in Bali is determined by experience, professional commitment, organizational commitment, idealism, and relativism by 82 percent, while the remaining 18 percent is determined by other factors. Keywords: Sensitivity ethics, experience, commitment, Orientation Ethics, and Public Accounting Firm in Bali